2019
DOI: 10.1186/s12887-019-1690-5
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal carriage among children under five in Accra, Ghana, five years after the introduction of pneumococcal conjugate vaccine

Abstract: Background The study objective was to determine the carriage and serotype distribution of Streptococcus pneumoniae among children in Accra, Ghana, five years after the introduction of the pneumococcal conjugate vaccine (PCV-13) in 2012. Methods Nasopharyngeal swab samples were collected from 410 children below 5 years of age in Accra, Ghana, from September to December, 2016. Pneumococcal isolates were identified by optochin sensitivity and bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 43 publications
11
47
1
Order By: Relevance
“…Interestingly, serotypes 23B, 35B, and 38 detected in our study have already been reported by Renner et al (2019) to be causal pathogens of IPD among children under five years in Ghana [ 7 ]. However, serotype 1 which is the number one cause of IPD in Ghana [ 40 , 41 ] was not detected among the strains of this study, consistent with other published carriage data from Ghana [ 10 , 20 , 42 , 43 ]. We did not detect serotype 19A, the eighth most prevalent serotype worldwide [ 37 ] but rather serotype 19B was detected.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Interestingly, serotypes 23B, 35B, and 38 detected in our study have already been reported by Renner et al (2019) to be causal pathogens of IPD among children under five years in Ghana [ 7 ]. However, serotype 1 which is the number one cause of IPD in Ghana [ 40 , 41 ] was not detected among the strains of this study, consistent with other published carriage data from Ghana [ 10 , 20 , 42 , 43 ]. We did not detect serotype 19A, the eighth most prevalent serotype worldwide [ 37 ] but rather serotype 19B was detected.…”
Section: Discussionsupporting
confidence: 91%
“…This is the first pneumococcal carriage study to be carried out in Cape Coast, Ghana. In this study, the pneumococcal carriage prevalence was 29.4%, which is lower when compared to the 54% [ 20 ] obtained from children attending nurseries and kindergartens in Accra, Ghana. This difference in carriage prevalence could be attributed to the variation in age distribution as well as the settings from which these children were recruited.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations